The evolving dynamics of airport ground access: A multinomial logit analysis of mode choice at Guwahati Airport, India - Lalit Swami; Mokaddes Ali Ahmed; Suprava Jena (Multimodal Transportation)
As shared mobility options like ridesourcing services continue to reshape urban transportation systems globally, their impact on airport ground access has become increasingly significant. This study investigates the changing dynamics of airport access at Lokpriya Gopinath Bordoloi International Airport (LGBI) in Guwahati, India, amidst the growing presence of ridesourcing services. A total of 700 air passengers were surveyed using a random sampling technique over 15 consecutive days, providing comprehensive data for the analysis. A multinomial logit (MNL) model was employed to examine factors influencing mode choice, considering variables such as age, residential status, group size, car ownership, luggage, safety, and convenience. The model explains 48.2 % to 57.2 % of the variation in mode choice. The results reveal that younger passengers (aged 21–30) are 2.14 times more likely to choose ridesourcing services. Additionally, visitors are significantly more inclined to use ridesourcing services compared to locals, with an odds ratio of 2.56. While passengers with car ownership are 5.43 times more likely to prefer private vehicles. The study underscores the growing significance of ridesourcing services in airport ground access and highlights the need for transportation planning and policymaking to adapt to these evolving trends.